The EN ISO 22000:2005 - Soares, N. (2016)
The purpose of an organization should be to ensure that their products can be consumed without constituting a health risk. The ISO 22000:2005 was structured in order to be applied to any organization operating in the food industry, by promoting the accountability of each operator for the guarantee of the product safety. The standard specifies the requirements necessary to implement a food safety management system (FSMS) that ensures the safety of food throughout the food chain. Each organization will need to assess how best to ensure compliance according to their specific situation and position in the food chain. There are many factors that pressure organizations to implement a FSMS. They can be divided into either internal or external pressures. The implementation of a FSMS which is periodically evaluated by external auditors facilitates, in many cases, the work of those who have to establish rules for the employees.